2020
DOI: 10.1108/ejim-04-2020-0146
|View full text |Cite
|
Sign up to set email alerts
|

The role of innovation capability in the relationship between marketing capability and new product development: evidence from the telecommunication sector

Abstract: PurposeThe purpose of this study is to examine the relationships between marketing and innovation capabilities and new product development (NPD), including the potential mediating and moderating roles of innovation capability (IC) in the relationship between marketing capability (MC) and NPD.Design/methodology/approachData were collected from telecommunication firms operating in the Kurdistan region of Iraq using a self-administered questionnaire. Of 556 distributed questionnaires, 272 were returned and used f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
21
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 74 publications
2
21
0
1
Order By: Relevance
“…Thus, it is suggested that SMEs must engage in IC to improve their performance. This finding is consistent with prior work (Aljanabi, 2020; Fan et al, 2021; Vakulenko, 2020) emphasizing the moderating role of IC. The final finding concerns the moderation effect of SMA.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Thus, it is suggested that SMEs must engage in IC to improve their performance. This finding is consistent with prior work (Aljanabi, 2020; Fan et al, 2021; Vakulenko, 2020) emphasizing the moderating role of IC. The final finding concerns the moderation effect of SMA.…”
Section: Discussionsupporting
confidence: 92%
“…Furthermore, Vakulenko (2020) evidenced the moderating role of IC between the limitations of small firm size and innovative output. Aljanabi (2020) corroborated the moderating effect of IC on the link between marketing capabilities and new product development in the telecommunication sector of Iraq. Further, Fan et al (2021) recently evidenced that IC significantly moderates the relationship between EO and SMEP in the SME setting in developing countries.…”
Section: Literature Reviewmentioning
confidence: 75%
See 2 more Smart Citations
“…Past research done on SMEs has shown that high levels of innovation are crucial to build EO (Miller, 1983). Higher innovation capability in the person could lead to a higher chance of building networks with partners and generate a huge variety of resources by the entrepreneur (Aljanabi, 2020; Ganguly et al , 2019; Ramachandran and Ramnarayan, 1993; Su et al , 2018). Studies done by Cho and Pucik (2005) find innovativeness related to the firm venturing into new arenas and increasing EO by enhancing the firm's opportunities in existing markets.…”
Section: Literature Reviewmentioning
confidence: 99%